2008
DOI: 10.1007/s00192-008-0650-7
|View full text |Cite
|
Sign up to set email alerts
|

Human urine with solifenacin intake but not tolterodine or darifenacin intake blocks detrusor overactivity

Abstract: The objective of the study was to evaluate the local effects of three antimuscarinics excreted into human urine after oral ingestion. Two normal adult collected their voided urine after taking oral doses of tolterodine, darifenacin, and solifenacin for 7 days with a 14-day washout period. The urodynamic effect of intravesically administered human urine on carbachol-induced bladder overactivity was studied in female rats. Cystometric parameters were measured during continuous infusion of saline and human urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Intravenous solifenacin has been reported to reduce the bladder afferent activity with the measurement of pelvic nerve spikes in rats (20). In addition, bladder instillation of carbachol induced decreases in bladder capacity, and intravesical human urine obtained after administration of solifenacin prevented carbacholinduced decreases in bladder capacity (21). In contrast, intravesical human urine obtained after administration of tolterodine and darifenacin showed no effect on bladder function.…”
Section: Effect On Bladder Afferent Pathwaysmentioning
confidence: 99%
“…Intravenous solifenacin has been reported to reduce the bladder afferent activity with the measurement of pelvic nerve spikes in rats (20). In addition, bladder instillation of carbachol induced decreases in bladder capacity, and intravesical human urine obtained after administration of solifenacin prevented carbacholinduced decreases in bladder capacity (21). In contrast, intravesical human urine obtained after administration of tolterodine and darifenacin showed no effect on bladder function.…”
Section: Effect On Bladder Afferent Pathwaysmentioning
confidence: 99%
“…Chuang et al showed that human urine obtained after taking solifenacin (5 mg) prevented the carbachol-induced detrusor overactivity. 18) Thus, the urine excreted after oral ingestion of solifenacin may provide a localized pharmacological advantage for the treatment of overactive bladder syndrome. The current study aimed to examine such hypothesis by measuring muscarinic receptor binding in the bladder urothelium and detrusor muscles of rats after intravesical instillation of solifenacin.…”
mentioning
confidence: 99%
“…25 A potential unique benefit of solifenacin among anticholinergics is that it is more selective than other antimuscarinics and has up to 15% of the medication secreted as an active metabolite into the urine and available for binding to receptors on the urothelium. 26,27 If incontinence does occur, then the active metabolite may potentially bind the urethral urothelium causing less irritation and decreasing the signals sent to the bladder causing instability. In addition, solifenacin did perform better than tolterodine ER in the European STAR trial, decreasing number of incontinence pads used, in which 14.7% were men.…”
Section: Discussionmentioning
confidence: 99%